2009
DOI: 10.1152/ajprenal.00010.2009
|View full text |Cite
|
Sign up to set email alerts
|

Changes of renal AQP2, ENaC, and NHE3 in experimentally induced heart failure: response to angiotensin II AT1receptor blockade

Abstract: Lü tken SC, Kim SW, Jonassen T, Marples D, Knepper MA, Kwon TH, Frøkiaer J, Nielsen S. Changes of renal AQP2, ENaC, and NHE3 in experimentally induced heart failure: response to angiotensin II AT 1 receptor blockade. Am J Physiol Renal Physiol 297: F1678 -F1688, 2009. First published September 23, 2009 doi:10.1152/ajprenal.00010.2009.-Heart failure (HF) was induced by ligation of the left anterior descending artery (LAD). Left ventricular end-diastolic pressure (LVEDP) Ͼ25 mmHg (at day 23 after LAD ligation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 62 publications
4
57
2
Order By: Relevance
“…In addition, a recent study by Lütken el at. (20) showed that candesartan treatment reduces the inner medullary AQP2 levels and reduces the apical targeting of APQ2 in CHF rats. Moreover, Wong and Tsui (36) demonstrated normalization of the increased inner medullary AQP2 expression in response to treatment with the angiotensin-converting enzyme (ACE) inhibitor enalapril in cardiomyopathic hamsters (36).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a recent study by Lütken el at. (20) showed that candesartan treatment reduces the inner medullary AQP2 levels and reduces the apical targeting of APQ2 in CHF rats. Moreover, Wong and Tsui (36) demonstrated normalization of the increased inner medullary AQP2 expression in response to treatment with the angiotensin-converting enzyme (ACE) inhibitor enalapril in cardiomyopathic hamsters (36).…”
Section: Discussionmentioning
confidence: 97%
“…10,11 Conversely, pharmacologic blockade of the AT 1 receptor reduces AQP2 expression in experimental heart failure. 9,23 In addition, Li et al 11 have recently shown that angiotensin II stimulates expression and trafficking of AQP2 proteins to the apical surface of immortalized principal cells. Our finding of an impaired response to vasopressin in CD-KOs supports a key interaction between AT 1A receptors in the collecting duct and V2 receptor activation of AQP2.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,23 To determine whether cellular localization of AQP2 to the apical membrane is altered in the CD-KOs, immunofluorescent labeling of AQP2 was analyzed by confocal microscopy. As shown in Figure 4, under baseline conditions with free access to water, AQP2 immunostaining in the inner medulla showed a weak and diffuse staining pattern that was similar in control ( Figure 4, A and E) and CD-KO ( Figure 4, B and F) mice.…”
Section: Cellular Localization Of Aqp2 In Cd-ko and Control Micementioning
confidence: 99%
“…An ACE inhibitor has been also reported to reduce the expressions of V2R and AQP-2 mRNA in the kidney of the cardiomyopathic hamster. 29 Recently, Lütken et al 30 demonstrated that increased expression of AQP2 as well as ENaC and NHE3 in postinfarcted rats with HF were, at least in part, reversed by AT1 receptor antagonism. AVP could potentially stimulate renin secretion directly via activation of V2R or indirectly through reduction of the sodium concentration at the macula densa.…”
Section: Renal Effect Of Tolvaptan In Hfmentioning
confidence: 99%